Outcome metrics in recommended performance measurement tools for emergency department performance evaluation: a systematic review - Tytti Kristiina Toukola; Reija Katri Kyllikki Mertanen; Johanna Marjut Kaartinen; Eeva Anneli Tuunainen; Maaret Kaarina Castrén; Paulus Mikael Torkki (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine)
Abstract Background There is no established protocol for measuring the overall performance of an emergency department (ED). This study sought to evaluate in terms of outcome measures the existing measurement tools created for ED use. Design A comprehensive systematic literature review was conducted following the PRISMA guidelines. A systematic literature search was performed in databases of Medline and Scopus using the following eligibility criteria: (1) article context is the hospital ED; (2) the purpose is to develop or use a measurement tool concerning either quality or value; (3) the measurement tool evaluates the overall ED performance; (4) the measurement tool consists of more than two single performance indicators; and (5) the article is published in English. Main results Fifteen unique articles met the eligibility criteria and were included in the systematic review. The Delphi method was the most popular method for identifying the recommended performance indicators for ED use. Ten articles defined outcome metrics as a separate category of indicators. The indicators perceived as outcome metrics differed widely among the studies. The outcome metrics recommended can be divided into the following five dimensions: reattendances, mortality, diagnostic and procedural errors and complications, diagnosis-specific survival rates, and patient experience. Forty-six single outcome metrics were identified. Reattendances were the most frequently recommended outcome metrics, with 20 single indicators falling into this category. Conclusions The lack of consensus on applicable outcome metrics makes it difficult to evaluate ED performance reliably. This study highlights the need to define and classify more specifically suitable outcome metrics for ED use to justify improvement actions and investigate the effect of healthcare reforms on ED operations. Registration PROSPERO CRD42023470855.